Aquisição do léxico em espanhol como língua estrangeira segundo a Teoria Holística da Atividade - Lima, Liara Josiane Rodrigues de (2010)
Language enables communication among human beings and according to Vygotskian theory it performs two important functions. First, it performs an interpersonal function. Subsequently, when language is internalized, besides promoting interaction, it guides people in the construction of their thoughts and becomes the basis for the emergence of conscience, having an intrapersonal function. In this context, mastering a considerable amount of words in a target language may contribute to a clear communication among the interlocutors and may be one of the resources to acquire the ability of writing good texts. In this sense, we have done a research with students of the course of Languages Portuguese/Spanish in order to verify to what extent a framework approach, among which we have opted for process-writing, has contributed for lexical acquisition of Spanish as a foreign language through textual productions. The main theoretical base was the Holistic Theory of Activity (RICHTER, 2004, 2005, 2006, 2008), so all the theoretical and methodological foundation adopted to analyze the corpus proceeded from this base. The corpus is composed by answers to a questionnaire and by texts produced by the students through process-writing, by White & Arndt (1991). The results obtained through the corpus analysis led us to conclude that there was an expansion of lexical items in the students texts and that they related this expansion to process-writing. During all this process, we observed that the students were at the same time expanding their vocabulary and then improving their writing as they noticed what was happening to them in each stage, i.e., the difficulties they had, the resources they sought and the strategies they used made them reflect on what may occur with their future students and then help these in their Zone of Proximal Development. In this view, the students not only wrote texts but also obtained grants to become mediators of this process.